Gardening for the homebrewer - Tweten, Wendy; Teashon, Debbie
"Gardening for the Homebrewer is an introduction to the wide variety of plants you can use for fermentations or infusions. Learn how to tell if your yard is a perfect site for barley or whether it's better suited to a fragrant collection of herbs. Learn how to grow, dry, and store fresh hops. Or go off the beaten path and grow everything you need for your first gruit, cider, perry, or fruit wine. Do you only have a balcony or a windowsill for your organic inspirations? No problem! A variety of plant recommendations will suit gardens and gardeners of all types, even ones with limited space."--
Before you begin -- The big beer ingredients: growing hops, malt, and other grains -- Other beer ingredients: brewing herbs and fermentables -- All sorts of wines: growing grapes and other fruits -- Cider: the lowdown on apples and other cider-friendly fruits -- A little bit of perry: a chapter for pears -- Liqueurs and infused spirits.
Keywords: Food crops; Plants, Edible; Plants, Useful; Beer; Wine and wine making